2022
DOI: 10.1002/cbdv.202200536
|View full text |Cite
|
Sign up to set email alerts
|

Annual Phytochemical Variations and Antioxidant Activity within the Aerial Parts of Lavandula angustifolia, an Evergreen Medicinal Plant

Abstract: Acknowledging the importance of medicinal compounds, flavonoids, and phenolic acids in plants and human health; understanding the best time to harvest plants to get the most potentially therapeutic biological activity; and predicting and controlling the quality of medicinal plants are very useful. The rich chemical composition of medicinal lavender, as well as its antioxidant activity, has led to its wide application in the pharmaceutical, cosmetic, and food industries. In the current research, seasonal differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…It is interesting to know that the total flavonoids, like the phenolic composition of quercetin, showed a decreasing trend, especially in the treatment of 1000 mg L −1 . In line with our results, the researchers found a direct relationship between some phenolic compounds and flavonoids [29] …”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…It is interesting to know that the total flavonoids, like the phenolic composition of quercetin, showed a decreasing trend, especially in the treatment of 1000 mg L −1 . In line with our results, the researchers found a direct relationship between some phenolic compounds and flavonoids [29] …”
Section: Resultssupporting
confidence: 93%
“…Likewise, a positive correlation between antioxidant activity and total phenol has been proven in mango, [28] and putrescine treatment increased their phenol content. Similar to our findings, with the foliar application of polyamines, a significant increase in the amount of total phenol and antioxidant capacity of rose was seen compared to control plants [29] . A study on yarrow reported that foliar application of fulvic acid improved antioxidant activity [11] …”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Lavender grows best in a hot and dry climate [ 5 ]. Harvest time can also affect the phenolic content of lavender, and plants harvested in summer and autumn have shown increased levels of essential oil compared to those plants harvested in winter and spring [ 8 ]. Lavender is edible, and lavender tinctures are used to treat a variety of ailments, as it has both antioxidant and antimicrobial properties [ 2 ].…”
Section: Introductionmentioning
confidence: 99%